CHARACTERIZATION OF THE LEMON-GRASS PRODUCTION IN THE PARANÁ STATE, BRAZIL - GOMES, Eliane Carneiro; NEGRELLE, Raquel Rejane Bonato; DONI FILHO, Luiz (Scientia Agraria, 2007)
Considering the importance of lemon-grass (Cymbopogon citratus (D.C.) Stapf) crop on the special products sector (medicinal plants, species and similars) of Paraná State (Southern Brazil), this work presents a characterization of the Parana lemon-grass production evidencing the congruence and incongruity of the observed procedures taking into consideration what is reported on literature as being proper for this crop. The main problems evidenced were linked with ignorance of the producers about many proper aspects related with the crop, including seedlings production/ obtaining; ideal time for plantation and harvesting to maximize biomass and quantity of active substances; control of plagues and diseases and, organic practices. The urgent need of transference of technical information to producers, including those relating to application of good agricultural practices of lemon grass crop was evidenced.